An approach to studying the neural correlates of reserve - Stern, Yaakov (Brain imaging and behavior, 2017)
The goal of this paper is to review my current understanding of the concepts of cognitive reserve (CR), brain reserve and brain maintenance, and to describe our group’s approach to using imaging to study their neural basis. I present a working model for utilizing data regarding brain integrity, clinical status, cognitive activation and CR proxies to develop analyses that can explore the neural basis of cognitive reserve and brain maintenance. The basic model assumes that the effect of brain changes on cognition is mediated by task-related activation. We treat CR as a moderator to understand how task-related activation might vary as a function of CR, or how CR might operate independently of these differences in task-related activation. My hope is that this presentation will spark discussion across groups that study these concepts, allowing us to come to some common agreement on definitions, methodology and approaches.